Please solve question no.7
Attachments:
![](https://hi-static.z-dn.net/files/dff/27ef2a69f472afa07cd69c292d758144.jpg)
Answers
Answered by
1
Hello user
x = a.sin○ and y = b.tan○
Squaring both of them we get...
x^2 = a^2.sin^2○
x^2/a^2 = sin^2○ ........(1)
Similarly, we get
y^2/b^2 = tan^2○ ...........(2)
Subtracting eq. 1 and 2 by reprocaling them,
we get..
a^2/x^2 - b^2/y^2 = 1/sin^2○ - 1/tan^2○
= (1-cos^2○)/(sin^2○)
since, 1-cos^2○ = sin^2○
So,
a^2/x^2 - b^2/y^2 = (sin^2○)/(sin^2○) = 1
Hence proved
-----------------------☆☆☆☆☆☆☆☆-------------------
x = a.sin○ and y = b.tan○
Squaring both of them we get...
x^2 = a^2.sin^2○
x^2/a^2 = sin^2○ ........(1)
Similarly, we get
y^2/b^2 = tan^2○ ...........(2)
Subtracting eq. 1 and 2 by reprocaling them,
we get..
a^2/x^2 - b^2/y^2 = 1/sin^2○ - 1/tan^2○
= (1-cos^2○)/(sin^2○)
since, 1-cos^2○ = sin^2○
So,
a^2/x^2 - b^2/y^2 = (sin^2○)/(sin^2○) = 1
Hence proved
-----------------------☆☆☆☆☆☆☆☆-------------------
Similar questions